The value impact of international and industrial diversifications on public‐listed firms in Malaysia - Lee, Kian Tek *; Hooy, C. W.; Hooy, G. K. (Elsevier, 2012)
This study examines the relationship between firm value and both international and industrial diversification involvements for a sample of 267 listed firms in Malaysia over 2001–2009. We find no evidence that international diversification has any significant impact on the firm value but industry diversification locally slightly increases firm value, even after controlling for the degree of ownership concentration. Our research further indicates that without any diversification involvement, family ownership presents lower value than foreign and government ownerships; and with industrial diversification family ownership presents significant higher value than foreign and government ownerships.